(untitled) (Innovation & Development in Engineering and Applied Science, 2023)
The implementation of a Geoportal has importance to Ecuadorian so- ciety since it allows to know the geospatial information of varying nature and application. The present research focuses on the development of a Geoportal which includes a map visualization where it is possible to see in detail the varied layers of important aspects of Ecuador. It allows the user to observe thematic maps according to diverse areas. The administrative module allows to manage the layers of the database by specifying to which topic they belong, therefore the process of generating and sample of the spatial information are automated. To implement the Geoportal, a platform with free software was used. Linux Centos 7 was selected as the base operating system. The technology used as map server was MapServer 7.0.1. For the map viewer, Pmapper 5 was chosen because of its ease of use and because it allows to include OpenLayer. Finally, the portal was developed using the Yii and Bootstrap framework. The research poses challenges to end users because when using this type of tools it is easy to obtain geospatial information very quickly.